Factor associated with anxiety disorder during covid-19 pandemic among college students - Nugrahaeni, Dyan Kunthi; Mauliku, Novie Elvinawaty; Saputra, Aditiyana Eka; Lakhal, Bashir Mabrok (University of Muhammadiyah Malang, 2023)
Coronavirus Disease-2019 (COVID-19) is a novel illness not previously identified in humans. Its unprecedented emergence has resulted in many effects on individuals, including the onset of anxiety. Therefore, this study aimed to identify factors associated with an anxiety disorder during the COVID-19 pandemic among college students. Using a snowball sampling technique, a quantitative design was employed to select 453 participants. The instruments used were the 7-point Generalized Anxiety Disorder scale and the Multidimensional Scale of Perceived Social Support. Furthermore, data analysis was carried out using the Chi-Square test and Pearson’s correlation. Several factors related to anxiety disorder include gender (p=0.001), year of study (p=0.001), teaching delivery method (p=0.049), sources of information about COVID-19 (p=0.009), family member affected (p=0.009) and social support (p=0.001). The results showed that social support had a negative correlation with anxiety disorder, support from family (r=-0.33, p=0.001),friends (r=-0.31, p=0.001), and significant others (r=-0.23, p=0.001). Therefore, factors associated with anxiety disorder during the pandemic were gender, study year, teaching delivery method, sources of information, affected family members, and social support.